Enhancing Fasting Safety in Ramadan for Adults and Adolescents with Type 1 Diabetes Mellitus through Optimal Diabetes Care - Abdulrahman Sulaiman S Alanazi, Hussain Nasser O Kariri (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Despite guidelines advising against fasting for individuals with type 1 diabetes during Ramadan, many choose to fast, posing risks of hypoglycemia, hyperglycemia, and diabetic ketoacidosis.Aim: This study aimed to assess the effects of optimal care, including Ramadan-focused education, flash glucose monitoring, dietary advice, and treatment adjustment, on the safety of Ramadan fasting in individuals with type 1 diabetes.Methods: Thirty participants with type 1 diabetes, opting to fast during Ramadan, were enrolled. Pre-Ramadan, all received specialized education and training for Freestyle Libre (FSL) sensor use. Participants utilized the sensor for 6 weeks (pre-Ramadan and during Ramadan). Physical and biological parameters were collected 2 to 4 weeks before and after Ramadan.Results: Among the 24 patients on basal bolus insulin and 2 on insulin pumps with FSL data, the average fasting period was 24 days. Ninety-five percent reported educational session benefits. No clinically significant changes in physical/biological data occurred pre/post-Ramadan, except for a reduction in HbA1c from 8.2% to 7.9% post-Ramadan (P=0.010). While 63% adjusted insulin doses during Ramadan, flash glucose monitoring revealed fewer hypoglycemic episodes (29.2% vs. 46.7% pre-Ramadan). One case of diabetic ketoacidosis occurred due to missed insulin doses to prevent hypoglycemia.Conclusion: Selective individuals with type 1 diabetes, receiving optimal care, demonstrated improved glycemic control and reduced hypoglycemia risk during Ramadan fasting. Larger, randomized controlled trials are necessary for generalizing these findings as recommendations.